Synthesis and characterisation of TiO2 nanoparticles using alkaline fusion method for potential photocatalyst application - Che Abdullah, Che Azurahanim; Norman, Ashreen; Muhd Yusop, Muhammad Azri; Mohd Khairuddin, Nur Farahah; Hazan, Roshasnorlyza (Inderscience Publishers, 2024)
The current research involves the preparation of titanium-based nanoparticles having potential for photocatalytic release of pollutants or dyes. The titanium dioxide (TiO2) nanoparticles were synthesised using an alkaline fusion method using natural ilmenite as a titanium precursor. Ultra-violet visible (UV-Vis) spectroscopy and powder X-ray fluorescence (XRF) were used to characterise the synthesised nanoparticles. The results indicated that increasing the calcination temperature decreased the degradation rate of methyl orange (MO) due to increased particle size and surface area. The photocatalytic degradation of MO established that TiO2 was an effective catalyst for dye removal from water samples.